Pilot Implementation of Floating Treatment Wetland Systems in Nagdaha, Nepal: Field Experience, Performance, and Lessons Learned - Byanju, Ayaswori; Kayastha, Sadhana Pradhanang; Dhungana, Bharat; Manandhar, Susa; Maharjan, Anjana; Pradhananga, Dhiraj (Journal of Hydrology and Meteorology, 2025)
Population growth and agricultural practices, excessive nutrients, and pollutants increasingly threaten surface water bodies and ecosystems. The Floating Treatment Wetland System (FTWS) is one of the nature-based remediation technologies consisting of a floating raft that supports phytoremediation plants, allowing roots to be suspended in the water column to remediate different pollutants from water. The study was conducted in Nagdaha, Lalitpur, to test the efficacy of FTWS in remediating polluted surface water. For this, 40 floating rafts of 1.2’ × 1.8’ (2.16 sq. ft.) each were constructed and planted with Canna indica (CI) and salvia Splendens (SS) that were strategically deployed on the lake at five different points, with each point consisting of eight rafts. Water quality parameters (nitrate, ammonia, phosphate, and iron) were monitored at all the installed points, including the inlet and outlet of the lake. During the five-month test period, the maximum nitrate reduction was 94% in the rafts installed at the northeast (NE) point, while the maximum iron reduction was 95% in the southeast (SE) point. In the case of ammonia, the maximum reduction was found to be 68% at the southwest (SW) point compared to the lake inlet. Statistical analysis revealed a significant difference (p < 0.05) only for nitrate concentration between inlet and outlet points, suggesting minimal impact on other parameters. The study indicated better survival of CI compared to SS, and floating rafts with CI enhanced the scenic beauty of the lake after blooming. These findings thus demonstrate the potential of FTWS as a sustainable and effective solution for water quality improvement and suggest that increasing the number of rafts could optimize the efficacy for broader applications in a similar type of context.